2016
DOI: 10.4103/0975-5950.201355
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate vertical bone dimension managed by indirect sinus grafting technique and simultaneous implant placement

Abstract: Implant placement into the posterior maxilla often creates a challenge due to inadequate bone height because of close sinus proximity. This article presents a case report of indirect sinus lift technique involving hydraulic pressure to elevate the floor of the maxillary sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The strength of osseointegration is usually determined by implant stability. 11,12,14,15,21 The mean initial ISQ values at surgery in both groups were 39.00±2.16 and 40.00±2.12, respectively, in this sample. The ISQ levels at the time of operation are low when compared to the values at 6 months, which are 70.43 and 68.71.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The strength of osseointegration is usually determined by implant stability. 11,12,14,15,21 The mean initial ISQ values at surgery in both groups were 39.00±2.16 and 40.00±2.12, respectively, in this sample. The ISQ levels at the time of operation are low when compared to the values at 6 months, which are 70.43 and 68.71.…”
Section: Discussionmentioning
confidence: 68%
“…The hydraulic lifter in the CAS kit, on the other hand, was not a very convenient. As a result, investigators concluded that sinus lift devices need to be improved or developed further to make them safer and more user-friendly 9,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation